2018
DOI: 10.1101/437525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental manipulation ofHeliconiuswarning patterns reduces harassment of previously mated females

Abstract: 9Why warning patterns are so diverse is an enduring evolutionary problem. Because predators 10 learn to associate particular patterns with unpleasant experiences, an individual's risk of 11 predation should decrease as the local density of its warning pattern increases. Heliconius 12 butterflies, however, are known for their diversity of warning patterns, and the establishment 13 of entirely new phenotypes is difficult to explain under strict frequency-dependent selection. 14 One possibility is that during per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Other mechanisms may generate gradual departure from the ancestral trait value and may also contribute to the diversity of mimetic traits: the evolution of aposematic signals in defended species away from those exhibited in Batesian mimics has been theoretically shown (Franks et al, 2009), but empirical evidence of such effect of Batesian mimicry is still lacking. Artificial modification of the warning trait of mated females has also been demonstrated to reduce harassment by males in the butterfly H. erato, and would therefore allow them to lay more eggs, suggesting that evolution of slightly divergent trait could be promoted in females (Merrill et al, 2018).…”
Section: Reproductive Interference Can Explain the Emergence Of Mimet...mentioning
confidence: 99%
“…Other mechanisms may generate gradual departure from the ancestral trait value and may also contribute to the diversity of mimetic traits: the evolution of aposematic signals in defended species away from those exhibited in Batesian mimics has been theoretically shown (Franks et al, 2009), but empirical evidence of such effect of Batesian mimicry is still lacking. Artificial modification of the warning trait of mated females has also been demonstrated to reduce harassment by males in the butterfly H. erato, and would therefore allow them to lay more eggs, suggesting that evolution of slightly divergent trait could be promoted in females (Merrill et al, 2018).…”
Section: Reproductive Interference Can Explain the Emergence Of Mimet...mentioning
confidence: 99%
“…For instance, heavier wood tiger moth females may be more prone to actively reject males than lighter females. Although this hypothesis should be properly tested, it has been already shown that in Lepidoptera male harassment can be costly to females (Merrill et al., 2018 ) and females actively reject males to the point they can override male preference (Chouteau et al., 2017 ). This behavioral hypothesis is also in line with the lowest yy female mate acceptance toward males carrying the W allele that lacks the deleterious elements associated with the y allele when expressed in homozygote yy males (at least for the reproductive success).…”
Section: Discussionmentioning
confidence: 99%